The Vatican’s Test Through Women, Gender, and Sexual Abuse in the Context of the Synod on Synodality - Osman Şahin (Darulfunun Ilahiyat)
The Roman Catholic Church faces a number of contemporary problems that are also partly global issues. The place of women in the Church, cases of sexual abuse, and the LGBTQ+ movement are some of these current issues for which the Vatican is trying to find a basis for agreement. The 16th Ordinary General Assembly of the Synod of Bishops was initiated by Pope Francis in 2021 under the theme “For a Synodal Church: Communion, Participation, and Mission.” This Synod is addressing within its scope a number of issues related to synodality, as well as solutions to the aforementioned pressing challenges. The Synod on Synodality is defined as a four-year process that ensures the participation of all the People of God. The Synod is placing particular emphasis on listening to women and those who feel excluded by the Church, and during the Synod a number of issues have stood. As anticipated, some of these issues involve women more actively participating in decision-making processes within the Church, establishing a deaconate for women, addressing the problem of sexual abuse, and welcoming LGBTQ+ individuals into the Church. This study aims to assess the issues raised in the Synod documents and to present the Vatican’s perspective and direction regarding these sensitive challenges.